Comparative antibiogram and clinical efficacy of neomycin in bovine genital infections - RAMPRABHU, R; RAJESWAR, J JOHNSON; PADMANABAN, C; AVADAYAPPAN, T (The Indian Journal of Animal Reproduction, 2023)
Microbial agents isolated from seventy-six cases of bovine genital infections and their antibiotic sensitivity patternwas recorded. E. coli was the most prevalent organism followed by Staphylococcus sp and Streptococcus sp. Maximum per centof genital isolates were sensitive to neomycin followed by gentamicin, amikacin and ciprofloxacin and were resistant totetracycline and kanamycin. In the treatment trial, single parentral administration ofneomycin resulted in 84.30% conceptionrate whereas animals treated with gentamicin resulted in 60% conception only.
Keywords: Bovine; genital infections; antibiotic sensitivity; neomycin